(untitled) (Annals of Medical Research, 2021)
There are controversial reports on the effect of sodium-potassium adenosine triphosphatase (Na+ -K+ ATPase) inhibition on mast cell mediator release. Some of them have indicated that ouabain (strophanthin G), a specific Na+ -K+ ATPase inhibitor, inhibited the release, whereas the others have shown that ouabain had no effect or even had a stimulatory effect on the mediator secretion. Most of these studies utilized animal-derived cells. The aim of this study was to determine the effect of Na+ -K+ ATPase inhibition on human skin mast cells. Unpurified and purified mast cells were obtained from newborn foreskins and stimulated by calcium ionophore A23187 (1 µM) for 30 min following a 1 hr incubation with various concentrations (10e-4 to 10e-8 M) of ouabain. Histamine release was assayed by enzyme immunoassay. The results indicated that ouabain, a Na+ -K+ ATPase inhibitor, had no significant effect on the non-immunologic histamine release from human skin mast cells in vitro and suggested differences between human and animal mast cells.